2019
DOI: 10.1016/j.livsci.2018.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Censored Bayesian models for genetic evaluation of age at first calving in Brazilian Brahman cattle

Abstract: We compared different Bayesian models to handle censored data for genetic parameters estimation of age at first calving (AFC) in Brazilian Brahman cattle. Data from females with AFC above 1825 days of age were assumed to have failed to calve and were considered as censored records. Data including information of 53,703 cows were analyzed through the following methods: conventional linear model method (LM), which consider only uncensored records; simulation method (SM), in which the data were augmented by drawin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Setiaji et al [ 39 ], analyzing different penalty methods to access interval from the first to the last successful insemination in Japanese Black heifers, concluded that EBV correlations decrease at higher levels of censored (missing) records. Using only uncensored data and the conventional linear model was also the most recommended method for the genetic evaluation of age at first calving in Brahman cattle [ 11 ]. However, the authors pointed out that similar EBV correlations were observed using either uncensored or penalized data, which suggests that there was not relevant re-ranking of animals when censored records were used [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Setiaji et al [ 39 ], analyzing different penalty methods to access interval from the first to the last successful insemination in Japanese Black heifers, concluded that EBV correlations decrease at higher levels of censored (missing) records. Using only uncensored data and the conventional linear model was also the most recommended method for the genetic evaluation of age at first calving in Brahman cattle [ 11 ]. However, the authors pointed out that similar EBV correlations were observed using either uncensored or penalized data, which suggests that there was not relevant re-ranking of animals when censored records were used [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using only uncensored data and the conventional linear model was also the most recommended method for the genetic evaluation of age at first calving in Brahman cattle [ 11 ]. However, the authors pointed out that similar EBV correlations were observed using either uncensored or penalized data, which suggests that there was not relevant re-ranking of animals when censored records were used [ 11 ]. Similarly, Costa et al [ 40 ] also found that the linear-threshold model without censored data showed the best predictive ability (computed based on the EBV correlation estimated between the complete and reduced datasets) for the genetic evaluation of both age at first calving and stayability in Nellore cattle.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations